STRUCTURAL AND FUNCTIONAL STABILITY OF ANTHROPOGENICALLY TRANSFORMED LANDSCAPES - Зеленчук, Іван (SWorldJournal, 2026)
Anthropogenically transformed landscapes are considered as geosystems within which the spatial–structural organization and the nature of interactions between inert, mobile, and living components change under the influence of construction-industrial devel